Conceptualising examinable physical education in the Irish context: Leaving Certificate Physical Education. Issue 7 (1st September 2020) - Scanlon, Dylan; MacPhail, Ann; Calderon, Antonio
ABSTRACT : A Physical Education Development Group (PEDG) was responsible for constructing a new school subject curriculum, Leaving Certificate Physical Education (LCPE), in Ireland. This paper provides an insight into this development group and explores the process of curriculum development, and the influence of roles and power-ratios within the group, in the construction of the LCPE curriculum. Figurational sociology concepts (Elias, 1978 ) were drawn on to make sense of the curriculum makers' experiences. Interviews were conducted with 10 PEDG members. The findings suggest that the members' roles had very little, if any, influence on the curriculum development process. Findings also revolved around the unbalanced power-ratios which existed in the PEDG and highlighted the socially powerful position of 'strong, well-established' (in the academic field of curriculum development – participant's words) members and the other members (predominantly representing practicing teachers). We express concern for the role of teachers in the curriculum process and argue that they play a crucial and significant role in the school subject curriculum development process. This paper supports Goodson's (1983) and Penney's (2006) conceptualisation of the contested and socially constructed nature of the curriculum development process.